PENINGKATAN KUALITAS PRODUK IKM RUMAH SABUN DENGAN PENDEKATAN QUALITY FUNCTION DEPLOYMENT - Enty Nur Hayati; Firman Ardiansyah Ekoanindiyo; Mohammad Riza Radyanto; Endro Prihastono (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
Companies that can meet the needs and desires of their consumers will usually be much more competitive compared to others, especially companies that can exceed the needs and desires of these consumers (Besterfield, 1999: 89). Rumah Soap is one of the UMKM that produces various kinds of liquid soap, including dishwash (dishwashing soap), liquid detergent, hand soap, shampoo, body foam, etc. The problem to be discussed in this research is how to design the needs and technical characteristics of consumers on liquid soap products. The objectives to be achieved are to identify the needs and technical characteristics of liquid soap products based on the HOQ, as well as to design liquid soap products that meet the needs of the community. The house of quality or also known as the House of Quality (HOQ) is the first stage in the application of the QFD methodology. The stages in the HOQ begin with identifying consumer needs and wants by determining Voice Of Customer (VOC), making a planning matrix, determining the level of customers in the competition, determining technical description (Voice Of Engineer), making a technical response matrix, determining the relationship between the attributes of needs and characteristics. technical (Inter Relation matrix), create a technical correlation matrix (draw a map of the interdependence and interrelationships between technical characters, company/organizational difficulties, technical benchmarks, create a target matrix. Consumers want 12 variables of need for laundry detergent which are dominated by needs in the category of product design and quality product characteristics. The QFD design shows detergent products, with the characteristic of "change in raw materials" as a priority technical characteristic that can improve the quality of laundry detergent with a Relative Importance Level (TKR) of 31.827%. To improve the quality of laundry detergent products, Rumah Soap UMKM should pay attention to the following proposals to produce laundry detergent.